Big data and innovation in tourism, travel, and hospitality managerial approaches, techniques, and applications - Rahimi, Roya.; Sigala, Marianna; Thelwall, Mike. (Singapore Springer Singapore Imprint: Springer, 2019)
"This book brings together multi-disciplinary research and practical evidence about the role and exploitation of big data in driving and supporting innovation in tourism. It also provides a consolidated framework and roadmap summarising the major issues that both researchers and practitioners have to address for effective big data innovation. The book proposes a process-based model to identify and implement big data innovation strategies in tourism. This process framework consists of four major parts: 1) inputs required for big data innovation; 2) processes required to implement big data innovation; 3) outcomes of big data innovation; and 4) contextual factors influencing big data exploitation and advances in big data exploitation for business innovation." --
Chapter 1. Big Data: the Oil of the New Tourism Economy -- Chapter 2. Composite Indicators for Measuring the Online Search Interest by a Tourist Destination -- Chapter 3. Developing Smart Tourism Destinations with the Internet of Things -- Chapter 4. Big Data in Online Travel Agencies and its Application Through Electronic Devices -- Chapter 5. Big Data for Measuring the Impact of Tourism Economic Development Programme: a Process and Quality Criteria Framework for Using Big Data -- Chapter 6. Research on Big Data, VGI, and the Tourism and Hospitality Sector: Concepts, Methods, and Geographies -- Chapter 7. Sentiment Analysis for Tourism -- Chapter 8. Location-Based Social Network Data for Tourism Destinations -- Chapter 9. Identifying Innovative Idea Proposals with Topic Models - A Case Study from SPA Tourism -- Chapter 10. Customer Data and Crisis Monitoring in Flanders and Brussels -- Chapter 11. Analyzing Airbnb Customer Experience Feedback Using Text Mining -- Chapter 12. Big Data as a Game Changer: How does it Shape Business Intelligence within a Tourism and Hospitality Industry Context? -- Chapter 13. Strengthening Relational Ties and Building Loyalty Through Relational Innovation and Technology: Evidence from Spanish Hotel Guests -- Chapter 14. Big Data and its Supporting Elements: Implications for Tourism and Hospitality Marketing.
Includes bibliographical references
Description based on publisher-supplied MARC data.
Keywords: Big data (Computer science); Tourism -- Management; Quantum computing; Big data (Analytics); Big data; Tourism management; Hospitality industry -- Management; Travel -- Management